Higiene Pengolah dan Pedagang serta Identifikasi Cemaran Salmonella sp pada Bakso Bakar di Teluk Binjai, Kota Dumai - Miranti Anada Putria; Dewi Erowati; Fitri Fitri; Lidya Novita (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2022)
The implementation of hygienic snacks starting from processing and serving is an important factor that must be considered by all food producers and sellers. Teluk Binjai in Dumay City has various vendors selling various kinds of snacks, one of which includes grilled meatballs. The purpose of this study was to see personal hygiene of processors and traders as well as the identification of Salmonella sp contamination in grilled meatballs in Teluk Binjai, Dumai City. There were three merchants found at the location. This type of research is descriptive observational with total sampling technique. In general, it was found that the processing staff and traders of grilled meatballs did not meet the personal hygiene requirements as only 40% processors that keep hand, hair and head clean. This can be caused by various factors such as lack of knowledge of processors and traders about the importance of application of good personal hygiene. All samples of grilled meatballs at traders did not contain Salmonella sp. However, this does not rule out the possibility of other microbiological contamination in grilled meatballs. There is a need for further research on the factors that influence the application of personal higiene in snack foods and the identification of other types of microbiology in grilled meatballs.